Crop storage efficiency and market competitiveness: Case of groundnut and cowpea in Ghana - Bediako, JA; Chianu, Jonas N.; Dadson, J.A. (2009)
Using groundnut (Arachis hypogea) and cowpea (Vigna unguiculata), this study empirically demonstrated the correlation between crop storage and economic competitiveness of producers, captured from the degree of market integration and producer shares of the prices paid by consumers, among others. Secondary data covering 1963–1997 were used and complemented with primary data. Results from analysis of market integration showed delayed information flow among groundnut and cowpea markets, especially the latter. This suggests the absence of perfect competition and negatively affects participation of smallholder farmers in profitable marketing of groundnut and cowpea, especially during the lean season. The Harris’ inverse margins from estimated equations indicated that cowpea traders, more than groundnut traders, colluded in pricing, implicating price determination outside the market forces. The attack by weevils [Callosobruchus maculatus (Fabricius)] and bruchids limits farmers’ success in storing cowpea, creating monopoly for traders with better storage facilities coupled with chemical treatments to reduce such attacks. Price spread estimations showed that groundnut unlike cowpea farmers enjoyed a larger share of consumers’ payments. The study concludes with recommendations on the need to intensify efforts in effective storage of agricultural commodities at the farm-level, as a way of improving the welfare of farm families without necessarily expanding the land area under cultivation.